Diagnosis difficulties of Fahr’s syndrome – case report - Kuśmierek, Maciej; Lechańska, Joanna; Helman, Bartłomiej; Talarowska, Monika; Florkowski, Antoni; Gałecki, Piotr (Current Problems of Psychiatry, 2011)
The aim of the paper was to present the diagnostic difficulties related to the diagnosis of Fahr syndrome. Accurate diagnosis requires extensive research, starting with an interview, through a clinical evaluation, the implementation of psychological tests, to a variety of additional tests and imaging.The paper is a description of the psychopathological picture, course of illness and subsequent stages of diagnosis of two patients with the diagnosis of Fahr syndrome hospitalized in the Department of Adult Psychiatry, Medical University of Lodz in 2009.The diagnosis of Fahr's syndrome can not be based solely on clinical picture, it is only an indication to perform a thorough diagnostic imaging. The study of choice is the CT of the head with the assessment of intracranial calcification foci. The studies with fluorodeoxyglucose PET, SPECT using 99mTc-HMPAO are also useful.